2021
DOI: 10.1007/s10895-021-02730-3
|View full text |Cite
|
Sign up to set email alerts
|

Group 14 Metallafluorenes as Sensitive Luminescent Probes of Surfactants in Aqueous Solution

Abstract: Sila-and germa uorenes containing alkynyl(aryl) substituents at the 2,7-position are strongly emissive with high quantum yields in organic solvents. Provided they are su ciently soluble in water, their hydrophobic structures have the potential for many biological and industrial applications in the detection and characterization of lipophilic structures. To that end, the emission behaviors of previously synthesized 2,7-bis[alkynyl(biphenyl)]-9,9-diphenylsila uorene (1), 2,7-bis[alkynyl(methoxynaphthyl)]-9,9diph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 24 publications
(31 reference statements)
2
12
0
Order By: Relevance
“…2,7-disubstituted sila-and germafluorenes (metallafluorenes, MFs) [17][18][19] (Scheme 1) have many of the above favorable photophysical properties due to the aromatic core with strong 𝜋 − 𝜋 stacking and tunable 2,7-substituents. In previous work, we demonstrated that this small library of 2,7-disubstituted sila-and germafluorenes interact with surfactant micelles, exhibiting impressive quantum yields in the presence of surfactants (approaching 100% quantum efficiency) and appreciable emission fold enhancements (5-25x) [20]. We also demonstrated that these compounds have specificity for lipid structures in yeast cells, colocalizing with the lipid droplet stain Nile Red [21].…”
Section: Introductionmentioning
confidence: 60%
“…2,7-disubstituted sila-and germafluorenes (metallafluorenes, MFs) [17][18][19] (Scheme 1) have many of the above favorable photophysical properties due to the aromatic core with strong 𝜋 − 𝜋 stacking and tunable 2,7-substituents. In previous work, we demonstrated that this small library of 2,7-disubstituted sila-and germafluorenes interact with surfactant micelles, exhibiting impressive quantum yields in the presence of surfactants (approaching 100% quantum efficiency) and appreciable emission fold enhancements (5-25x) [20]. We also demonstrated that these compounds have specificity for lipid structures in yeast cells, colocalizing with the lipid droplet stain Nile Red [21].…”
Section: Introductionmentioning
confidence: 60%
“…Proc. 2022, 4, x luminescent in aqueous solution and exhibit high quantum yields and dramatic emi enhancements in the presence of various surfactants (5-25-fold) [10]. These results su that MFs could have biological applications.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, they are non-toxic to cells and can enter cells and colocalize with Nile Red, a lipid probe. In addition, the higher extinction coefficients of MFs and competitive quantum yields [10] make them more sensitive. All of these observations bode well for the application of MFs as lipid probes both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations